การส่งเสริมสุขภาวะผู้สูงอายุในโรงเรียนผู้สูงอายุชุมชนดงมะดะ จังหวัดเชียงราย - พระสุนิล, จามรี (Area Based Development Research Journal, 2018)
This study aims to promote the overall health of Elderly in Senior School Dongmada Sub-district. Key informant was 30 elderly citizens who are members of different elderly clubs in Dongmada sub-district (60 years old). Methodology were observation process, In-depth interview and the community stage for focus groups, analyze data with the elderly on the potential development approach leadership health and to promote the well-being of the elderly. The development of the potential of the elderly focuses on the development of knowledge from the local wisdom and cooperation in the network. Overall, building a network of social and cultural knowledge and other support agencies as Dongmada District Municipality Educational institution Public Health Department. Leadership in community health development focuses on being a leader in the community that represents the well-being for immunity to change. The elderly accept old experts in the city (Traditional Healers) and community leaders such as Por Luang (headman). Promoting health and Well-being in the elderly are important a holistic health approach, whereof family and community. The advantage Dongmada's are the relationship of the elderly, cooperation and promoting the network. As well activities in the Senior School support the healthy development of Elderly. Well-being through self-reliance, resilience, and immunity and improve the quality of their physical and mental health. For example, there are excellent caregivers for the elderly, studying herb, folk medicine, recreation and disseminate knowledge.